Control over training process as the basis of successful realization of elite handball teams’ training - Tyshchenko, V.O. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: substantiation of control over elite handball players’ training functioning with the help of special tests. Material: experiment covered 85 elite handball players of 18-32 yrs. old age (teams of Supreme League of Ukrainian championship). Results: effectiveness of different means and methods of control over sportsmen’s fitness have been studied. The following tests have been offered: vertical jump, test-balance, shuttle run, test for accuracy of throws, «T-test», «Bеер-тест». Model characteristics of indicators of qualified sportsmen’s fitness have been determined. A list of test exercises, which are rather effective for control over handball training, has been recommended. Conclusions: testing of special workability of qualified handball players permitted to assess current condition of sportsmen, their functional potentials; it also allowed to determine symptoms of de-adaptation and to differentiate correction of training program.